Analisis Dan Perencanaan Strategi Sistem Informasi Pada LLDIKTI Wilayah II Palembang - Abi Zidan; Dicky Pratama (BETRIK, 2026)
The advancement of Information Systems and Information Technology (IS/IT) requires organizations to improve service quality effectively and efficiently. The Higher Education Service Institution (LLDIKTI) Region II Palembang, as an institution responsible for supervising private universities, requires integrated information systems. However, current conditions indicate that IS/IT utilization is not fully optimized, as shown by limited system integration, lack of real-time data management, and the absence of structured IS/IT strategic planning. This study aims to develop IS/IT strategic planning aligned with organizational needs using the Ward and Peppard approach. The analysis employs Value Chain, PEST, SWOT, and Critical Success Factors (CSF) to evaluate internal and external environments. The results include IS strategy, IT strategy, and IS/IT management strategy, along with application portfolio recommendations and a development roadmap. These outcomes are expected to enhance service performance, support data-driven decision-making, and accelerate digital transformation within LLDIKTI Region II Palembang.